Recommendations for cervical cancer screening programs in developing countries: the need for equity and technological development Recomendaciones a programas de detección oportuna de cáncer cervical en países en desarrollo: necesidad de equidad y desarrollo tecnológico - Eduardo Lazcano-Ponce; Patricia Alonso; José Antonio Ruiz-Moreno; Mauricio Hernández-Avila (Instituto Nacional de Salud Pública, 2003)
The cervical cancer screening programs (CCSP) have not been very efficient in the developing countries. This explains the need to foster changes on policies, standards, quality control mechanisms, evaluation and integration of new screening alternatives considered as low and high cost, as well as to regulate colposcopy practices and the foundation of HPV laboratories. Cervical cancer (CC) is a disease most frequently found in poverty-stricken communities and reflecting a problem of equity at both levels gender and regional, and this, is not only due to social and economic development inequalities, but to the infrastructure and human resources necessary for primary care. For this reason, the CCSP program must be restructured, a) to primarily address unprivileged rural and urban areas; b) to foster actions aimed at ensuring extensive coverage as well as a similar quality of that coverage in every region; c) to use screening strategies in keeping with the availability of health care services. In countries with a great regional heterogeneity, a variety of screening procedures must be regulated and standardized, including a combination of assisted visual inspection, cervical cytology and HPV detection; d) regional community intervention must be set up to assess the effectiveness of using HPV detection as an strategy in addition to cervical cytology (pap smear); e) the practice of colposcopy must be regulated to prevent the use of it in healthy women at a population level, thus preventing unnecessary diagnosis and treatment which not only are expensive but also causes unnecessary anxiety to women at risk; f) the operation of those clinical laboratories using HPV as a detection strategy must likewise be accredited and regulated and g) the CCSP program for assuring health care quality should meet the expectations of its beneficiaries, and increase the knowledge in cervical cancer related matters. Finally, though a variety of clinical tests on prophylactic and therapeutic vaccines against HPV are recently being developed worldwide; it will take at least from 5 to 10-years time to have them available in the market. For this reason, it will be necessary to intensify the CCSP programs. All these reasons lay emphasis on the need to reinforce actions for CCSP programs. Los programas poblacionales de detección oportuna de cáncer cervical (DOC) han sido poco eficientes en países en desarrollo. Por esta razón, es necesario impulsar cambios en las políticas, normatividad, mecanismos de control de calidad, evaluación e integración de nuevas alternativas de tamizaje consideradas de bajo y alto costo, así como la regulación de la práctica de colposcopía y de la futura integración de laboratorios para el VPH. El cáncer cervicouterino (CC) es una enfermedad de la pobreza que refleja un problema de equidad de género y de equidad regional, no sólo en cuanto a diferencias de desarrollo económico y social, sino en cuanto a la infraestructura física y de recursos humanos que otorgan servicios de atención primaria. Por esta razón, un programa de DOC debe reorganizarse para: a) dirigirse predominantemente a regiones geográficas rurales y urbanas marginadas, b) impulsar acciones que garanticen una cobertura ampliada y calidad similar en todas las regiones, c) utilizar estrategias de tamizaje acordes con la disponibilidad de servicios de atención médica. En países con gran heterogeneidad regional deben regularse y normarse diversos escenarios de tamizaje que incluyan la combinación de imagen visual asistida, citología cervical y determinación del VPH, d) se deben iniciar intervenciones comunitarias regionales que evalúen la efectividad de utilizar el VPH como estrategia adicional a la citología cervical (Pap), e) se debe regular la práctica de la colposcopía para evitar su utilización en mujeres sanas a nivel poblacional, y así, evitar sobre-diagnóstico y sobre-tratamiento, que no sólo tienen implicaciones de elevados costos, sino que producen ansiedad innecesaria en las mujeres en riesgo, f) debe acreditarse y regularse la práctica de los laboratorios clínicos que determinen el VPH como estrategia de detección, y g) el programa de DOC para garantizar calidad, también deberá satisfacer las expectativas de las usuarias, así como aumentar el conocimiento sobre cáncer cervical. Finalmente, a pesar de que diversos ensayos clínicos de vacunas profilácticas y terapéuticas contra el VPH se desarrollan actualmente a nivel mundial al menos durante un periodo de entre 5 y 10 años las vacunas contra este virus no estarán disponibles comercialmente. Por esta razón, será necesario reforzar las acciones de los programas de DOC.